INTERPRETATION OF THE QURAN WITH A PHILANTROPHIC APPROACH (TAFSIR AT-TANWIR STUDY BY MAJELIS TARJIH DAN TAJDID PP MUHAMMADIYAH) - Rochmah, Nur Hafifah; Munir, Ahmad (QiST: Journal of Quran and Tafseer Studies, 2023)
The purpose of this study is to find out the method of interpreting the book of Tafsir At-Tanwir, how to interpret the verses about philanthropy in Tafsir At-Tanwir, and the contextualization of philanthropic verses with social welfare. This study used the library research method with a descriptive-analytical approach. The author uses the thematic method to reveal the contents of the Al-Quran more comprehensively. The results of the study show that Tafsir At-Tanwir combines the tahlili and mawdu'i methods simultaneously (tahlili cum-thematic). The interpretation of philanthropic verses in Tafsir At-Tanwir tries to awaken the spirit of Islamic philanthropy which is built through the spirit of the Al-Quran. Philanthropy is a manifestation of the concept of charity theology with the spirit of al-Mauninitiated by KH Ahmad Dahlan, namely worship is not only of mechanical-ritualist-individualist value but of practical action that also has universal value within a frame of social piety. Islamic philanthropy has enormous potential in realizing social welfare. The actualization of teachings on philanthropy can help improve the lives of people in need and reduce social inequality.